Activism, Bioethics and Academic Research. (25th April 2019) - Draper, Heather
Abstract: This article sketches a taxonomy of the activities in which bioethics academics engage, including activities that may make their own research more impactful, from little or no engagement outside academia to activism or extreme activism. This taxonomy, the first of its kind, may be useful in determining what obligations bioethics academics have in relation to activism and activities that fall short of activism.